response of microbial biomass and hydrolytic enzymes to a decade of nitrogen, phosphorus, and potassium addition in a lowland tropical rain forest - Turner, Benjamin L; Joseph Wright, S (Biogeochemistry, 2014)
Nutrient availability is widely considered to constrain primary productivity in lowland tropical forests, yet there is little comparable information for the soil microbial biomass. We assessed microbial nutrient limitation by quantifying soil microbial biomass and hydrolytic enzyme activities in a long-term nutrient addition experiment in lowland tropical rain forest in central Panama. Multiple measurements were made over an annual cycle in plots that had received a decade of nitrogen, phosphorus, potassium, and micronutrient addition. Phosphorus addition increased soil microbial carbon (13 %), nitrogen (21 %), and phosphorus (49 %), decreased phosphatase activity by ~65 % and N-acetyl β-glucosaminidase activity by 24 %, but did not affect β-glucosidase activity. In contrast, addition of nitrogen, potassium, or micronutrients did not significantly affect microbial biomass or the activity of any enzyme. Microbial nutrients and hydrolytic enzyme activities all declined markedly in the dry season, with the change in microbial biomass equivalent to or greater than the annual nutrient flux in fine litter fall. Although multiple nutrients limit tree productivity at this site, we conclude that phosphorus limits microbial biomass in this strongly-weathered lowland tropical forest soil. This finding indicates that efforts to include enzymes in biogeochemical models must account for the disproportionate microbial investment in phosphorus acquisition in strongly-weathered soils.